Aging in Cats: Owner Observations and Clinical Finding in 206 Mature Cats at Enrolment to the Cat Prospective Aging and Welfare Study - Dowgray, Nathalie; Pinchbeck, Gina; Eyre, Kelly; Biourge, Vincent; Comerford, Eithne; German, Alexander J. (Frontiers in Veterinary Science, 2022)
Two hundred and six cats, aged between 7-10 years, from the North-west of the UK, were enrolled in a cat ageing and welfare study to determine the frequency of age-related conditions and associations with husbandry, owner observations of physical appearance, activity and behaviour. This is the largest study to date of mature cats that includes data from an owner questionnaire and clinical examinations. At enrolment, owners frequently reported physical changes (53%), behavioural changes (47%), changes to eating patterns (41%) and activity changes (40%) in their mature cats. On physical examination, 45% cats were in overweight condition and 12% were obese. A heart murmur was detected in 29% cats, whilst indirect systolic blood pressure (SBP) was >160 mmHg in 5% cats. Dental disease was present in 54% cats and was associated with a matted hair coat (P=0.01), increased sleeping (P=0.02), absence of grey hairs (P=0.03) and increased irritability to other pets (P=0.04). Abnormalities were evident in 58% of cats that allowed an orthopaedic examination (OE) to be performed. These cats were older than cats with a normal OE (P=0.01), and abnormal OE findings were associated with a matted coat (P=0.03) and increased grooming (P=0.04). Aazotaemia was present in 10% cats, and this was associated with cats being observed to ‘sniff their food and then walk away’ (P=0.04). Hyperthyroidism was diagnosed in 3% cats, who were older (P=0.02), had a leaner BCS (P=0.02) and lesser blood creatinine concentrations (P=0.01). Hyperthyroid cats were also more likely to have increased liver enzyme activity and increased SBP (P=<0.001) compared with non-hyperthyroid cats. Of the 176 cats where all clinical assessments were conducted, only 12% had no evidence of any disease. Clinical abnormalities are commonly identified when thorough, clinical assessments are performed in mature pet cats visiting primary care practice.